2014
DOI: 10.1159/000367640
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Multiple Sclerosis

Abstract: Background: The incidence of multiple sclerosis (MS) is increasing, particularly in young women (20−40 years). In line, experience in the management of pregnancies and use of disease-modifying therapy (DMT) in women with MS is accumulating. Summary: Fertility is generally not affected in MS. If assisted reproduction techniques (ART) are required, unsuccessful procedures are associated with an increased relapse risk, particularly in the first few months post-ART. During pregnancy, the risk of relapse declines c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 7 publications
5
58
1
4
Order By: Relevance
“…A recent study also reported that parity was not independently associated with secondary progression in 277 pregnant MS women with a median disease duration of 17 years [4]. In summary, present data have supported that pregnancy is generally safe for MS patients [5,6,7]. …”
Section: Introductionsupporting
confidence: 78%
“…A recent study also reported that parity was not independently associated with secondary progression in 277 pregnant MS women with a median disease duration of 17 years [4]. In summary, present data have supported that pregnancy is generally safe for MS patients [5,6,7]. …”
Section: Introductionsupporting
confidence: 78%
“…A U.S. study of women with spinal cord injury found no significant differences between pre- and post-injury pregnancies with regard to the proportions of miscarriages [5]. Similarly, data from Germany indicated that women with multiple sclerosis were not at increased risk of miscarriage [33]. Our multivariable regression analysis did suggest that disability was not as strong a predictor of miscarriage as maternal age, marital status, or health status.…”
Section: Discussionmentioning
confidence: 53%
“…These patients experience clinical improvement during pregnancy followed by a temporary ‘rebound’ exacerbation postpartum. Increased levels of a variety of pregnancy-related factors including estrogens (i.e., estradiol and estriol) are detected in maternal blood during pregnancy and many, including cortisol, progesterone, vitamin D, early pregnancy factor, and α-Fetoprotein, have been shown to be immunomodulatory and possess potential neuroprotective properties[82]. Estrogens downregulate the T cell-mediated adaptive immune response, simultaneously activate the innate immune response that tolerates, supports, and regulates fetal development, and confer neuroprotection and reduce relapses in pregnant women with MS[83].…”
Section: Estrogens and Msmentioning
confidence: 99%